Analisis Karakteristik dan Persepsi Pengguna Pelayanan Terhadap Pemanfaatan Puskesmas Sebagai Gatekeeper di Dua Puskesmas Kota Bekasi Tahun 2016 - Wulandari, Fitria Kusumawati; Achadi, Anhari (UI Scholars Hub, 2017)
The concept of primary health care in the era of National Health Insurance (JKN) is developed by strengthening primary health care as a gatekeeper with the concept of managed care. In this concept of managed care, one og the success story of the gatekeeper system is assessed by the visit and referral rates to the Higher Level of Health Facilities (ALHF/Fasilitas Kesehatan Tingkat Lanjut). This study aimed to determine the characteristics and perception of service users towards utilization of public health centers (PHC/Puskesmas) as gatekeeper in two PHC in City of Bekasi. This study used cross-sectional design and data collection by filling up questionnaires by 208 patients of JKN members in two health centers in Bekasi with stratified purposive sampling methods. The results showed that job (p=0.018), perceptions of the health workers’ attitudes (p=0.000), and treatment duration (p=0.048) were related to the utilization of PHC as a gatekeeper. Perceptions of the health workers’ attitude was the dominant factor affecting the utilization of PHC as a gatekeeper (r=0.720). The health workers’ attitude affected the repeated utilization services in PHC and its utilization as a gatekeeper, especially for continuum care. The proper application of gatekeeper concept should be able to increase the utilization of PHC and reduce the number of referrals to the Advanced Level of Health Facilities (ALHF).